Efficient Removal of Paracetamol by Manganese Oxide Octahedral Molecular Sieves (OMS-2) and Persulfate - Tepe, Ozlem; Tunc, Zeynep; Yildiz, Burcin; Sahin, Mehmet (Springer Int Publ Ag, 2020)
Pharmaceutically active compounds are gradually increasing in different environments such as surface waters, groundwater, and soil. Paracetamol is a pharmaceutical used as a pain reliever and antipyretic. In this study, paracetamol removal was investigated using manganese oxide octahedral molecular sieves (OMS-2) and persulfate. In the first stage of the study, OMS-2 was produced in a laboratory, and then paracetamol removal was investigated in OMS-2 only, persulfate only, and a combination of OMS-2/PS. When using 5 mM persulfate and 0.1 g/L OMS-2, the paracetamol removal efficiency increased to 99.5%. The use of OMS-2 with persulfate resulted in faster and more effective removal of paracetamol compared with OMS-2 only and persulfate only. In another stage of the study, the effects of reaction temperature and pH were investigated. For this purpose, the pH was changed in the range of 2-8, while the temperature was examined at 20, 30, and 40 degrees C. A high rate of paracetamol removal occurred at all pH and temperature values tested. Paracetamol removal was investigated at different OMS-2 and persulfate concentrations, optimum OMS-2 amount was determined as 0.1 g/L, and optimum persulfate dosage was 20 mM. The reusability of the OMS-2 catalyst was investigated, showing a decrease in removal efficiency with each cycle. In the later stages of the study, free radical quenching studies, the effect of humic acid and inorganic anions and the characterization of the synthesized OMS-2 were performed.
Keywords: Catalytic removal; OMS-2; Persulfate; Paracetamol; XPS